ANALISIS PELAKSANAAN PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI SMK NEGERI 1 BUNGURAN TIMUR KABUPATEN NATUNA PROVINSI KEPULAUAN RIAU - Rosalin Agustini; Sumarno Sumarno; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is aims to analyze of the implementation of practical and entrepreneurship learning at SMK Negeri 1 Bunguran Timur. The method used in this study is a mix method of qualitative and quantitative. The data collection methods used are observation, interview and documentation. The observation are performed during the implementation of practical and entrepreneurship learning. The interviews were conducted with teachers and students for more informations. The implementation of practical and entrepreneurship learning at SMK Negeri 1 Bunguran Timur are good. The teacher uses the scientific learning for practical and entrepreneurship learning. The learning model used by teacher is discovery learning, observations applied by teacher for student learning are experiments through practical. The entrepreneurial spirit among students is starting to grow with practical and entrepreneurship learning.Key Words: Implementation of Learning, Practical and Entrepreneurship Learning